2015
DOI: 10.1097/mnh.0000000000000130
|View full text |Cite
|
Sign up to set email alerts
|

Modeling hypercalciuria in the genetic hypercalciuric stone-forming rat

Abstract: Purpose of Review In this review we discuss how the Genetic Hypercalciuric Stone-Forming (GHS) rats, which closely model idiopathic hypercalciuria and stone formation in humans, provide insights into the pathophysiology and consequences of clinical hypercalciuria. Recent Findings Hypercalciuria in the GHS rats is due to a systemic dysregulation of calcium transport, as manifest by increased intestinal calcium absorption, increased bone resorption and decreased renal tubule calcium reabsorption. Increased lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…GHS rats have alterations in Ca homeostasis including increased intestinal absorption, reduced renal tubular reabsorption, and increased bone resorption, similar to those of many patients with idiopathic IH [24]. Hypercalciuria in the GHS rats leads directly to stone formation as it does in humans [1,37,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GHS rats have alterations in Ca homeostasis including increased intestinal absorption, reduced renal tubular reabsorption, and increased bone resorption, similar to those of many patients with idiopathic IH [24]. Hypercalciuria in the GHS rats leads directly to stone formation as it does in humans [1,37,39].…”
Section: Discussionmentioning
confidence: 99%
“…GHS rats were generated by selectively inbreeding Sprague-Dawley rats for increased uCa excretion [24]. When fed a standard, ample Ca diet, each GHS rat now consistently excretes over tenfold more uCa than Sprague-Dawley rat controls [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has identified loss of function mutations in CYP24A1, encoding the vitamin D-24-hydroxylase which regulates the catabolism of 1,25(OH) 2 D, can result in high circulating levels of 1,25(OH) 2 D, hypercalcemia, hypercalciuria, and nephrolithiasis in humans [50]. Our, and other team’s, studies using genetic hypercalciuric stone-forming rats showed that vitamin D could take part in the pathogenesis of urolithiasis [51,52,53]. Vitamin D receptor knockdown in genetic hypercalciuric rats reduced calcium phosphate deposits in the kidneys [52].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the cellular and molecular basis for alterations in bone formation and resorption in hypercalciuria while controlling for genetic, nutritional, and hormonal factors, we conducted studies in rats from an inbred colony of hypercalciuric rats . These genetic hypercalciuric stone‐forming (GHS) rats are the result of over 100 generations of selective inbreeding of hypercalciuric offspring of the original spontaneously hypercalciuric male and female Sprague–Dawley (SD) rats.…”
Section: Introductionmentioning
confidence: 99%